Pengetahuan Remaja Tentang Pengaruh Merokok Terhadap Kesehatan Gigi Dan Mulut - Gasril, Pratiwi; Aldo, Arif (As-Shiha: Jurnal Kesehatan, 2022)
Smoking is a risk factor for the occurrence of several types of diseases, both local and systemic. Tar, nicotine, and carbonmonoxide are the three most dangerous chemical ingredients in cigarette smoke. Objective: This study aims to find out a picture of adolescent knowledge about the dangers of smoking to dental and oral health. Research Method: This study uses a descriptive method, using a sampling technique with a random sampling technique, consisting of 78 respondents, by collecting data using a questionnaire. Research Results: Based on the research conducted and the data obtained in this study, it was obtained that as many as 54 respondents (69.2%) had good knowledge, 10 respondents (12.8%) had sufficient knowledge and 14 respondents (17.9%) were in the category of lack of knowledge. Conclusion : The conclusions in this study show that adolescent knowledge RW 07 is categorized as Good.